1976
DOI: 10.1083/jcb.68.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Purification from black widow spider venom of a protein factor causing the depletion of synaptic vesicles at neuromuscular junctions.

Abstract: The aqueous extract of the venom glands of black widow spiders was fractionated on a column of Sephadex G-200 and then on a column of DEAE-Sephadex A-50, pH 8.2. A protein fraction was obtained that caused a great increase in the frequency of occurrence of miniature end plate potentials at the frog neuromuscular junction, and caused swelling of the nerve terminals and depleted them of their vesicles. The fraction consists of at least four protein components that are similar in their molecular weights (about 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
139
3
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(149 citation statements)
references
References 34 publications
6
139
3
1
Order By: Relevance
“…It has been found that the venom of the black widow spider contains not only the well-characterized a-latrotoxin, (a-LTx), but also a fraction that appears to be toxic only t o arthropods (96). The primary effect of a-LTx is the stimulation of massive transmitter release with irreversible depletion of transmitter reserves (97).…”
Section: Toxins and Venomsmentioning
confidence: 99%
“…It has been found that the venom of the black widow spider contains not only the well-characterized a-latrotoxin, (a-LTx), but also a fraction that appears to be toxic only t o arthropods (96). The primary effect of a-LTx is the stimulation of massive transmitter release with irreversible depletion of transmitter reserves (97).…”
Section: Toxins and Venomsmentioning
confidence: 99%
“…A class of neurotoxins is known to act presynaptically (5,15,22,27). Among these, a-latrotoxin (a-LTx),' from the venom of the black widow spider, was found to act on many, and possibly all, types of vertebrate synapses, where it induces massive stimulation of quantal release of neurotransmitter accompanied by parallel depletion of synaptic vesicles (9,16,22,24,29,41,45). In contrast, a-LTx is completely inactive on axons and on nonneural cells, irrespective oftheir specific properties (secretion, excitability, etc .)…”
mentioning
confidence: 99%
“…␣-Latrotoxin stimulates neurotransmitter release from vertebrate nerve terminals by triggering massive exocytosis of small synaptic vesicles (1,2). ␣-Latrotoxin-stimulated neurotransmitter release is accompanied by presynaptic membrane depolarization and the influx of Ca 2ϩ through ion channels induced by the toxin (3,4).…”
mentioning
confidence: 99%